2015
DOI: 10.1115/1.4028308
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Structural Damage Identification Robustness to Noise and Damping With Integrated Bistable and Adaptive Piezoelectric Circuitry

Abstract: The accurate and reliable identification of damage in modern engineered structures is essential for timely corrective measures. Vibration-based damage prediction has been studied extensively by virtue of its global damage detection ability and simplicity in practical implementation. However, due to noise and damping influences, the accuracy of this method is inhibited when direct peak detection (DPD) is utilized to determine resonant frequency shifts. This research investigates an alternative method to detect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…In addition, the authors have developed a bifurcation-based sensing approach that can accurately determine damage-induced resonance frequency changes for vibration-based damage identification. 26 In conjunction with the data enrichment technique using adaptive piezoelectric circuitry, this prior study has shown significant enhancement in damage identification performance against noise contamination. However, since vibration-based techniques are generally limited to only low-frequency operation, the approach may not be effective for identifying incipient small-sized damages.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition, the authors have developed a bifurcation-based sensing approach that can accurately determine damage-induced resonance frequency changes for vibration-based damage identification. 26 In conjunction with the data enrichment technique using adaptive piezoelectric circuitry, this prior study has shown significant enhancement in damage identification performance against noise contamination. However, since vibration-based techniques are generally limited to only low-frequency operation, the approach may not be effective for identifying incipient small-sized damages.…”
Section: Introductionmentioning
confidence: 92%
“…[30][31][32][33] Recently, the bifurcation-based sensing approach has been extended to applications in macro-scale structures by introducing the required strong non-linearity through a strategic integration of bistable circuitry with piezoelectric transducer and the monitored structure. 26,34,35 While promising, such an approach has not been utilized for impedance-based measurement and SHM enhancement. In this research, we employ the bifurcation phenomena in a network of bistable circuits to develop a new sensing method that enables accurate measurement of damage-induced impedance changes against noise contamination for structural damage identification.…”
Section: Impedance Change Measurement Using Bifurcations In Bistable mentioning
confidence: 99%
“…The bistable circuit involves saddle-node bifurcation that activates sudden transitions between the intrawell and interwell oscillations. As a result, bistable circuits have been applied for various bifurcation-based applications [37,39,[55][56][57][58][59]. Since this bistable circuit design exhibits negligible backward coupling due to the characteristics of op-amp, it is suitable to utilize as a signal conditioning device that has little effect on the input signal [37].…”
Section: Experimental Investigationsmentioning
confidence: 99%
“…By leveraging unmistakable and sudden variations in sensor behavior due to subtle perturbations to the system which induce the bifurcation, the bifurcation-based sensing methods yield significantly enhanced resolution and sensitivity compared to conventional, linear dynamics-based detection methods. To introduce these novel and high performance detection principles into the context of meso-/macro-scale mechanical and civil structural health and condition monitoring, the authors recently integrated double-well Duffing circuits with the monitored systems [45,46]. In this way, small changes in the (assumed) linear dynamics of the monitored structures may activate more dramatic shifts in the circuit behaviors, providing a robust and sensitive framework for structural monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…1. Moreover, it is the double-well Duffing analog circuit that has been recently utilized as a bifurcation-based sensing device for detecting structural changes and damage in macroscale structures [45,46]. Thus, the analysis on stochastic and dynamic activation of the bifurcation directly provides an important means of characterizing the dynamics of practical bifurcation-based sensor platform.…”
Section: Introductionmentioning
confidence: 99%